The Typology of Babad Zaman (Chronicle of Times) Discourse in the Perspective of Mikhail Mikhailovic Bakhtin - Ikhwan, Ikhwan (TAWARIKH, 2015)
ABSTRACT: Nusantara or Indonesian archipelagoâs ancient manuscript is a precious cultural inheritance of the past. Apart from the content, that includes various topics concerning the life of society in the past, it also becomes a part of the tradition that constructs the recent society of Nusantara. One of the witnesses to the struggle of Nusantaraâs past Islamic society, in spreading Islam, is âBabad Zamanâ (BZ) or Chronicle of Timesâ manuscript. Observing from the content aspect, the manuscript is regarded distinctive. If generally Islamic manuscripts are taken from Arab, either copies or adaptations, BZ manuscript is an original work of the people in Nusantara. The author tried to contextualize the Islamic basic teaching concerning faith to the local context of Cirebon in West Java. Its tradition is a combination of three different traditions: Islam, Hindu, and Javanese beliefs. The paper specifically studies the form of discourse in the manuscript. The method employed is a discourse typology approach in the perspective of Mikhail Mikhailovic Bakhtin. The result of the research shows that BZ manuscript does not only contain either a single-voiced discourse or a double-voiced discourse, but it also contains a plural-voiced discourse. The discourse is differentiated into two types: linear discourse and parallel discourse. The linear discourse consists of vertical transmissive speech and horizontal transmissive speech, while the parallel discourse consists of contaminative speech and deflecting speech. The findings of the research complement the previous studies on Mikhail Mikhailovic Bakhtinâs double-voiced discourse in his work entitled âProblems of Dostoevskyâs Poeticsâ (1984).KEY WORDS: Chronicle of Times, Nusantaraâs Islamic manuscripts, Bakhtinian discourse analysis, double-voiced discourse, and polyphony.About the Author: Ikhwan, M.Hum. is a Doctoral Student at the Graduate Program, Faculty of Humanities UNPAD (Padjadjaran University) Bandung, Jalan Raya Jatinangor-Sumedang Km.21, West Java, Indonesia. For academic interests, the author is able to be contacted via e-mail at: ikhwanikhwan08@yahoo.comHow to cite this article? Ikhwan. (2015). âThe Typology of Babad Zaman (Chronicle of Times) Discourse in the Perspective of Mikhail Mikhailovic Bakhtinâ in TAWARIKH: International Journal for Historical Studies, Vol.7(1) October, pp.15-32. Bandung, Indonesia: Minda Masagi Press, ISSN 2085-0980.Chronicle of the article: Accepted (January 2, 2015); Revised (May 20, 2015); and Published (October 28, 2015).